2014
DOI: 10.1080/02701367.2014.983448
|View full text |Cite
|
Sign up to set email alerts
|

Elite Female Athletes' Ventilatory Compensation to Decreased Inspired O2During the Wingate Test

Abstract: Under hypoxic conditions, the ventilatory response to the Wingate test is perhaps more important than aerobic capacity per se in determining whether or not Wingate performance is decremented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…Consequently, E peak increased in HYP, as a compensatory response aiming to maintain oxygen consumption. In accordance, previous studies observed that the magnitude of the ventilatory response appears a critical factor of performance during a Wingate test in hypoxia (Fallon et al, 2015 ). Indeed, the authors showed that ventilation was elevated at the beginning and throughout the exercise when F i O 2 was decreased from 20.9 to 10% (Fallon et al, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, E peak increased in HYP, as a compensatory response aiming to maintain oxygen consumption. In accordance, previous studies observed that the magnitude of the ventilatory response appears a critical factor of performance during a Wingate test in hypoxia (Fallon et al, 2015 ). Indeed, the authors showed that ventilation was elevated at the beginning and throughout the exercise when F i O 2 was decreased from 20.9 to 10% (Fallon et al, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…These findings indicate that peak and relative to body mass anaerobic power have not been discriminating variables in futsal players' performance belonging to different categories. Fallon et al (2014) demonstrated that elite female football players obtained a mean value of 533 W in peak anaerobic power.…”
Section: Resultsmentioning
confidence: 98%
“…They performed a Wingate anaerobic test to determine maximal power (Wmax) (15). The Wingate Test has been used as a major test of muscle power whereas isokinetic devices have been used to determine muscle strength (16). The Wingate Test is commonly known as a method for measuring peak anaerobic power (PP) and mean anaerobic power (PM) (17).…”
Section: Introductionmentioning
confidence: 99%